Preliminary investigations of a dynamically deforming target-in-gel dosimeter. (August 2019) - Watson, C J; Yeo, A U; Supple, J R; Geso, M; Kron, T; Franich, R D
Abstract: To increase the clinical utility of deformable gel dosimeters an X-ray CT visible target region is introduced into the DEFGEL dosimeter, with the goal to enable the determination of the change in marginal doses around planned boundaries. The production of the dosimeter components is detailed and the requirements in making, deforming, irradiating and analysing the dosimeter are explored with several areas of required improvement identified. A single degree of motion is used to deform the dosimeter with the intent of identifying the volumetric dose changes caused by the deformation. The planned target volume dose structure was registered to the physical target region present in an optical CT data array and the dose volume histograms of the target volume while static and undergoing deformation are investigated and reported. The total dose to the target volume was shown to decrease by 9.4% due to a 1cm compression of the entire dosimeter volume. Further ways to improve the use of the target region are suggested with a view to improving the dose map information that can be obtained from target-in-gel dosimeters.